Financial capability an enhancement to extrinsic motivation in public service - Hortillo, Jose Neil Martizano (National College of Public Administration and Governance, University of the Philippines Diliman, 2019)
It is often argued that poor performance of public service can be due to the much lower salary pay among public servants compared to their counterparts in the private sector . In the Philippines, this issue is addressed through an incentive mechanism - such as periodic increases in salary through the salary standardization law (SSL) and performance-based bonus